Prediction of RCF clustered cracks dimensions using an ACFM sensor and influence of crack length and vertical angle. Issue 1 (2nd January 2020) - Shen, J.; Zhou, L.; Rowshandel, H.; Nicholson, G.L.; Davis, C.L.
ABSTRACT: Rolling contact fatigue (RCF) cracks are the predominant reason for rail grinding maintenance and replacement on all types of railway system, as they can potentially cause rail break if not removed. To avoid excessive material removal, accurate crack sizing is required. Alternating current field measurement has been used as an electromagnetic method for RCF crack sizing, incorporating with modelling results for single RCF cracks with large vertical angles (>30°). No study using this knowledge to size shallow angled crack clusters has yet been reported. A novel method, the pocket length compensation method, is proposed to determine the length and depth of RCF cracks with shallow vertical angles. For shallow crack clusters, vertical angle predictions are close to the measured values with a deviation of less than 13.6%. Errors in crack pocket length prediction are greatly reduced when the pocket length compensation was included. The predicted vertical depth using the approach developed for clustered angled cracks is accurate with errors <8.3%, which compares to errors of up to 60% if the single RCF crack approach is used and errors of up to 21.4% if a non-compensated prediction for crack clusters is used.